Forecast verification : a practitioner's guide in atmospheric science - Jolliffe, I. T.; Stephenson, David B. (Hoboken : John Wiley & Sons, 2012)
Forecast Verification: A Practioner's Guide in Atmospheric Science, 2nd Edition provides an indispensible guide to this area of active research by combining depth of information with a range of topics to appeal both to professional practitioners and researchers and postgraduates. The editors have succeeded in presenting chapters by a variety of the leading experts in the field while still retaining a cohesive and highly accessible style. The book balances explanations of concepts with clear and useful discussion of the main application areas.
5.2 Forecast examples5.3 First-order moments; 5.3.1 Bias; 5.3.2 Mean Absolute Error; 5.3.3 Bias correction and artificial skill; 5.3.4 Mean absolute error and skill; 5.4 Second- and higher-order moments; 5.4.1 Mean Squared Error; 5.4.2 MSE skill score; 5.4.3 MSE of scaled forecasts; 5.4.4 Correlation; 5.4.5 An example: testing the 'limit of predictability'; 5.4.6 Rank correlations; 5.4.7 Comparison of moments of the marginal distributions; 5.4.8 Graphical summaries; 5.5 Scores based on cumulative frequency; 5.5.1 Linear Error in Probability Space (LEPS); 5.5.2 Quantile-quantile plots.
5.5.3 Conditional quantile plots.
Print version record.
Keywords: Weather forecasting -- Statistical methods; Weather forecasting -- Statistical methods -- Evaluation; Geology; Science; Physics; NATURE -- Weather; SCIENCE -- Earth Sciences -- Meteorology & Climatology; Weather forecasting -- Statistical methods; Electronic books